Diffusion Processes and Fertility Transition: Selected Perspectives - National Research Council (The National Academies Press, 2001)
This volume is part of an effort to review what is known about the determinants of fertility transition in developing countries and to identify lessons that might lead to policies aimed at lowering fertility. It addresses the roles of diffusion processes, ideational change, social networks, and mass communications in changing behavior and values, especially as related to childbearing. A new body of empirical research is currently emerging from studies of social networks in Asia (Thailand, Taiwan, Korea), Latin America (Costa Rica), and Sub-Saharan Africa (Kenya, Malawi, Ghana). Given the potential significance of social interactions to the design of effective family planning programs in high-fertility settings, efforts to synthesize this emerging body of literature are clearly important.

Understanding and Preventing Violence, Volume 3: Social Influences - National Research Council (The National Academies Press, 1994)
This volume examines social influences on violent events and violent behavior, particularly concentrating on how the risks of violent criminal offending and victimization are influenced by communities, social situations, and individuals; the role of spouses and intimates; the differences in violence levels between males and females; and the roles of psychoactive substances in violent events.

Toward an Understanding of Metropolitan America: Report of the Social Science Panel on the Significance of Community in the Metropolitan Environment of the Advisory Committee to the Dept. of Housing and Urban Development, Assembly of Behavioral and Socia - National Research Council (The National Academies Press, 1974)

Panel on the 2000 Census: A Letter Report - National Research Council (The National Academies Press, 2000)

Enhancing Organizational Performance - National Research Council
Total quality management (TQM), reengineering, the workplace of the twenty-first century2014the 1990s have brought a sense of urgency to organizations to change or face stagnation and decline, according to Enhancing Organizational Performance. Organizations are adopting popular management techniques, some scientific, some faddish, often without introducing them properly or adequately measuring the outcome. Enhancing Organizational Performance reviews the most popular current approaches to organizational change2014total quality management, reengineering, and downsizing2014in terms of how they affect organizations and people, how performance improvements can be measured, and what questions remain to be answered by researchers. The committee explores how theory, doctrine, accepted wisdom, and personal experience have all served as sources for organization design. Alternative organization structures such as teams, specialist networks, associations, and virtual organizations are examined. Enhancing Organizational Performance looks at the influence of the organization's norms, values, and beliefs2014its culture2014on people and their performance, identifying cultural \

The New Year's Eve Flood on Oahu, Hawaii: December 31, 1987 - January 1, 1988 - National Research Council (The National Academies Press, 1991)
The flood that greeted the new year in 1988 brought home the uncomfortable realization that many suburban areas of eastern Oahu are at risk from sudden and, in some cases, unpredictable flooding. Torrential rains fell over the southeastern portion of the island on New Year's Eve, precipitating major flooding in several suburban neighborhoods and resulting in 34 million in damages. Neither the current meteorological capabilities nor the present flood control structures for the Oahu area proved adequate to predict or control the deluge. This book documents and analyzes the meteorological conditions leading to the torrential rains, the causes and patterns of flooding, the performance of flood control structures in affected areas, the extent of damages, and the effectiveness of the local emergency response and recovery actions. Conclusions and recommendations are drawn from the analyses.

Demographic Effects of Girls' Education in Developing Countries: Proceedings of a Workshop–in Brief - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2017)
Educating girls is a universally accepted strategy for improving lives and advancing development. Girls2019 schooling is associated with many demographic outcomes, including later age at marriage or union formation, lower fertility, and better child health. However, the causal pathways between education and demographic outcomes are not well understood. To advance understanding of the relationships between girls2019 education and demographic outcomes and to encourage more research on the determinants, content, context, and consequences of girls2019 education the National Academies of Sciences, Engineering, and Medicine conducted a workshop addressing these issues on May 11 and 12, 2017. This publication briefly summarizes the presentations and discussions from the workshop.

Using Linked Census, Survey, and Administrative Data to Assess Longer-Term Effects of Policy: Proceedings of a Workshop—in Brief - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2016)
The United States has seen major changes in recent decades in family structures, gender roles, immigration pat- terns, occupational and industrial patterns, and labor markets. All of these factors2014and others2014affect people2019s long-term health, social status, educational attainment, and economic opportunity. At the same time, the country2019s capacity to monitor trends and make long-term evidence-based policy to effect positive change has languished. The American Opportunity Study (AOS) is envisioned to create an intergenerational panel2014using existing data at the person level2014to study both social and economic mobility and the effectiveness of programs and policies that affect that mobility. It will develop the capacity to link existing data as needed for approved research purposes within a secure data environment. To begin work on the AOS, the National Academies of Sciences, Engineering, and Medicine established the Standing Committee on Creating the American Opportunity Study. To begin its work, the committee has explored the feasibility of capturing names of the people in the 1990 census and convened its first workshop. The committee2019s goal for the workshop, held on May 9, 2016, in Washington, D.C., was to more fully explore the value and potential uses of the AOS throughout a broad range of social science research. The committee also wanted to explore researchers2019 data needs and how those might converge with the vision for the AOS. This report summarizes the presentations and discussions from the workshop.

Leveraging Advances in Social Network Thinking for National Security: Proceedings of a Workshop - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2018)
Beginning in October 2017, the National Academies of Sciences, Engineering, and Medicine organized a set of workshops designed to gather information for the Decadal Survey of Social and Behavioral Sciences for Applications to National Security. The third workshop focused on advances in social network thinking, and this publication summarizes the presentations and discussions from this workshop.

Engineering Societies' Activities in Promoting Diversity and Inclusion: Proceedings of a Workshop–in Brief - National Academy of Engineering; National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2018)
As part of a series of workshops on the role of engineering societies in engineering education in the United States, the National Academy of Engineering held a workshop titled 201cEngineering Societies2019 Activities in Promoting Diversity and Inclusion201d on June 4, 2018. The goals were to explore how engineering societies can promote diversity and inclusion in engineering, provide an opportunity for societies to share promising practices, and investigate possible collaborative actions. This publication summarizes the presentations and discussions from the workshop.

Alerting America: Effective Risk Communication: Summary of a Forum - National Research Council (The National Academies Press, 2003)
This is a summary of presentations and discussion from a forum on risk communication convened by the Natural Disasters Roundtable. Issues related to risk communication were discussed at the forum by speakers and participants from the scientific community, local and federal agencies, and media organizations. The need for more research and actions to further the nation2019s risk communication capacity and make communities less vulnerable to natural, technological, and human-induced disasters was an overarching theme of the day. This summary is authored by Ruxandra Floroiu, formerly of the National Research Council and by Richard T. Sylves, University of Delaware.

Dynamic Social Network Modeling and Analysis: Workshop Summary and Papers - National Research Council (The National Academies Press, 2003)
In the summer of 2002, the Office of Naval Research asked the Committee on Human Factors to hold a workshop on dynamic social network and analysis. The primary purpose of the workshop was to bring together scientists who represent a diversity of views and approaches to share their insights, commentary, and critiques on the developing body of social network analysis research and application. The secondary purpose was to provide sound models and applications for current problems of national importance, with a particular focus on national security. This workshop is one of several activities undertaken by the National Research Council that bears on the contributions of various scientific disciplines to understanding and defending against terrorism. The presentations were grouped in four sessions 2013 Social Network Theory Perspectives, Dynamic Social Networks, Metrics and Models, and Networked Worlds 2013 each of which concluded with a discussant-led roundtable discussion among the presenters and workshop attendees on the themes and issues raised in the session.

Science and Engineering Programs: On Target for Women? - National Research Council (The National Academies Press, 1992)
Based primarily on a conference, this book examines the need for interventions to increase the number of U.S. students, both males and females, pursuing careers in the sciences and engineering and describes interventions supported by the private and public sectors at the undergraduate and graduate levels of education. The individually authored chapters also describe actions taken by employers of scientists and engineers to retain their technical work force.

Toward a National Health Care Survey: A Data System for the 21st Century - Institute of Medicine; National Research Council (The National Academies Press, 1992)
The nation's health care system has changed dramatically and the country is debating further significant changes. Comprehensive information is needed to guide policymakers in understanding and evaluating the current problems and in formulating federal health care policy. This book contains an evaluation of the plan developed by the National Center for Health Statistics for restructuring its existing provider surveys. It identifies current and future data needed by researchers and policymakers to assess the effect of changes in financing, organization, and delivery of health care on access, quality, costs, and outcomes of care and determines the extent to which the design and content of the proposed survey can meet these data needs. The book goes beyond a simple review and recommends a design framework to develop a coordinated and integrated data system to gather information about people and their illness over time and to link this information to costs and health care outcomes.

Education and Delinquency: Summary of a Workshop - National Research Council; Institute of Medicine (The National Academies Press, 2000)
The Panel on Juvenile Crime: Prevention, Treatment, and Control convened a workshop on October 2, 1998, to explore issues related to educational performance, school climate, school practices, learning, student motivation and commitment to school, and their relationship to delinquency. The workshop was designed to bring together researchers and practitioners with a broad range of perspectives on the relationship between such specific issues as school safety and academic achievement and the development of delinquent behavior. Education and Delinquency reviews recent research findings, identifies gaps in knowledge and promising areas of future research, and discusses the need for program evaluation and the integration of empirical research findings into program design.

Understanding Violence Against Women - National Research Council (The National Academies Press, 1996)
Violence against women is one factor in the growing wave of alarm about violence in American society. High-profile cases such as the O.J. Simpson trial call attention to the thousands of lesser-known but no less tragic situations in which women's lives are shattered by beatings or sexual assault. The search for solutions has highlighted not only what we know about violence against women but also what we do not know. How can we achieve the best understanding of this problem and its complex ramifications? What research efforts will yield the greatest benefit? What are the questions that must be answered? Understanding Violence Against Women presents a comprehensive overview of current knowledge and identifies four areas with the greatest potential return from a research investment by increasing the understanding of and responding to domestic violence and rape: What interventions are designed to do, whom they are reaching, and how to reach the many victims who do not seek help. Factors that put people at risk of violence and that precipitate violence, including characteristics of offenders. The scope of domestic violence and sexual assault in America and its conequences to individuals, families, and society, including costs. How to structure the study of violence against women to yield more useful knowledge. Despite the news coverage and talk shows, the real fundamental nature of violence against women remains unexplored and often misunderstood. Understanding Violence Against Women provides direction for increasing knowledge that can help ameliorate this national problem.

Human Factors Specialists'Education and Utilization: Results of a Survey - National Research Council (The National Academies Press, 1992)
Does the education given by the nation's human factors graduate training programs meet the skill and knowledge needs of today's employers? Can the supply of trained human factors specialists be expected to keep pace with the demand? What are the characteristics, employment settings, gender distribution, and salaries of human factors specialists? These and other questions were posed by the committee as it designed mail-in and computer-aided telephone surveys used to query human factors specialists. The committee evaluates its findings and makes recommendations aimed at strengthening the profession of human factors. This book will be useful to educators as an aid in evaluating their graduate training curricula, employers in working with graduate programs and enhancing staff opportunities for continuing education, and professionals in assessing their status in relation to their colleagues.

Human Factors Research Needs for an Aging Population - National Research Council (The National Academies Press, 1990)
This book describes the demographic, sociological, and ecological background of the aging society, identifies human factors problems associated with aging, summarizes currently relevant information, and recommends directions for research. It suggests a program of research and technology development for the purpose of ameliorating the effects of functional changes that accompany the aging process and provides a basis for additional research and application of human factors engineering data to the design of environments in which aging people must function.

A Strategy for Assessing Science: Behavioral and Social Research on Aging - National Research Council (The National Academies Press, 2007)
A Strategy for Assessing Science offers strategic advice on the perennial issue of assessing rates of progress in different scientific fields. It considers available knowledge about how science makes progress and examines a range of decision-making strategies for addressing key science policy concerns. These include avoiding undue conservatism that may arise from the influence of established disciplines; achieving rational, high-quality, accountable, and transparent decision processes; and establishing an appropriate balance of influence between scientific communities and agency science managers. A Strategy for Assessing Science identifies principles for setting priorities and specific recommendations for the context of behavioral and social research on aging.

The New Americans: Economic, Demographic, and Fiscal Effects of Immigration - National Research Council (The National Academies Press, 1997)
This book sheds light on one of the most controversial issues of the decade. It identifies the economic gains and losses from immigration2014for the nation, states, and local areas2014and provides a foundation for public discussion and policymaking. Three key questions are explored: What is the influence of immigration on the overall economy, especially national and regional labor markets? What are the overall effects of immigration on federal, state, and local government budgets? What effects will immigration have on the future size and makeup of the nation's population over the next 50 years? The New Americans examines what immigrants gain by coming to the United States and what they contribute to the country, the skills of immigrants and those of native-born Americans, the experiences of immigrant women and other groups, and much more. It offers examples of how to measure the impact of immigration on government revenues and expenditures2014estimating one year's fiscal impact in California, New Jersey, and the United States and projecting the long-run fiscal effects on government revenues and expenditures. Also included is background information on immigration policies and practices and data on where immigrants come from, what they do in America, and how they will change the nation's social fabric in the decades to come.